Reconstitution and NMR Characterization of the Ion-Channel Accessory Subunit Barttin in Detergents and Lipid-Bilayer Nanodiscs - Viennet, Thibault; Bungert-Plümke, Stefanie; Elter, Shantha; Viegas, Aldino; Fahlke, Christoph; Etzkorn, Manuel (Frontiers in Molecular Biosciences, 2019)
Barttin is an accessory subunit of ClC-K chloride channels expressed in the kidney and the inner ear. Main functions of ClC-K/barttin channels are the generation of the cortico-medullary osmotic gradients in the kidney and the endocochlear potential in the inner ear. Mutations in the gene encoding barttin, BSND, result in impaired urinary concentration and sensory deafness. Barttin is predicted to be a two helical integral membrane protein that directly interacts with its ion channel in the membrane bilayer where it stabilizes the channel complex, promotes its incorporation into the surface membrane and leads to channel activation. It therefore is an attractive target to address fundamental questions of intermolecular communication within the membrane. However, so far inherent challenges in protein expression and stabilization prevented comprehensive in vitro studies and structural characterization. Here we demonstrate that cell-free expression enables production of sufficient quantities of an isotope-labeled barttin variant (I72X Barttin, capable to promote surface membrane insertion and channel activation) for NMR-based structural studies. Additionally, we established purification protocols as well as refolding strategies in detergent micelles and phospholipid bilayer nanodiscs. Stability, folding and NMR data quality are reported as well as a suitable assignment strategy, paving the way to its structural characterization.